2014
DOI: 10.1118/1.4898596
|View full text |Cite
|
Sign up to set email alerts
|

Application of a radiophotoluminescent glass dosimeter to nonreference condition dosimetry in the postal dose audit system

Abstract: A set of RGD output correction factors was determined for field size changes and wedge insertions. The results obtained from recent postal dose audits were analyzed, and the mean differences between the measured and stated doses were within 0.5% for every field size and wedge angle. The SDs of the distribution were within the estimated uncertainty, except for one condition that was not reliable because of poor statistics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…kQnr,Qfnr,fref is a field‐size correction factor that corrects the differences between the conditions of field size of f ref and f nr . Several studies reported the energy and field‐size dependence for RPLD because of changes in the photon‐energy spectrum . Mizuno et al.…”
Section: Introductionmentioning
confidence: 99%
“…kQnr,Qfnr,fref is a field‐size correction factor that corrects the differences between the conditions of field size of f ref and f nr . Several studies reported the energy and field‐size dependence for RPLD because of changes in the photon‐energy spectrum . Mizuno et al.…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of the beams (43 beams) were within ±3%. Only one beam exceeded the tolerance level of ±5% [11]. The exact value of this 10 MV beam was +6.1%.…”
Section: Resultsmentioning
confidence: 99%
“…I i , E q and P q were determined before the audit trial started. The accumulated uncertainty of each parameter was estimated to be 1.1% in one standard deviation [11]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations